Igor Viktorovich Venin and His Contribution to the Design of Russian Defibrillators - V. A. Vostrikov; B. B. Gorbunov (Общая реаниматология, 2013)
On August 5, 2013 Igor Viktorovich Venin was 75 years old and devoted about 50 years of his life to medical electronic instrumentation engineering. In 1966 to 2012, sixteen defibrillator models including one with an unipolar pulse and 15 with bipolar pulses, out of them 6 current models with three (quasi-sinusoidal, trapezoidal, and quasi-sinusoidal step-functional) types of bipolar pulses were designed and put into serial production under the direction of I. V. Venin. The key achievement of I.V. Venin is that he developed the world’s first defibrillators with a bipolar pulse 24 years earlier than in the USA. This all amounts to about one half of the total number of defibrillators designed and transferred to production in the USSR, Russia, and Ukraine in 1952 to 2012. Key words: I.V. Venin, defibrillator, bipolar pulses.